Functional status in older patients with cancer and a frailty risk profile: A multicenter observational study. Issue 8 (November 2022) - Meert, Glen; Kenis, Cindy; Milisen, Koen; Debruyne, Philip R.; De Groof, Inge; Focan, Christian; Cornélis, Frank; Verschaeve, Vincent; Bachmann, Christian; Bron, Dominique; Den Bulck, Heidi Van; Schrijvers, Dirk; et al.
Abstract: Introduction: Functional status (FS) and frailty are significant concerns for older adults, especially those with cancer. Data on FS (Activities of Daily Living [ADL]; Instrumental Activities of Daily Living [IADL]) and its evolution during cancer treatment in older patients and a frailty risk profile are scarce. Therefore, this study examines FS and its evolution in older patients with cancer and a frailty risk profile and investigates characteristics associated with functional decline. Material and Methods: This secondary data-analysis, focusing on FS, uses data from a large prospective multicenter observational cohort study. Patients ≥70 years with a solid tumor and a frailty risk profile based on the G8 screening tool (score ≤ 14) were included. A geriatric assessment was performed including evaluation of FS based on ADL and IADL. At approximately three months of follow-up, FS was reassessed. Univariable and multivariable logistic regression analyses were used to identify predictive factors for functional decline in ADL and IADL. Results: Data on ADL and IADL were available at baseline and follow-up in 3388 patients. At baseline 1886 (55.7%) patients were dependent for ADL, whereas 2085 (61.5%) patients were dependent at follow-up. Functional decline was observed in 23.6% of patients. For IADL 2218 (65.5%) patients were dependent for IADL, whereas 2591 (76.5%) patients were dependent at follow-up. Functional decline in IADL was observed in 41.0% of patients. In multivariable analysis, disease stage III or IV, comorbidities, falls history in the past twelve months, and FS measured by IADL were predictive factors for functional decline in both ADL and IADL. Other predictive factors for functional decline in ADL were polypharmacy, Eastern Cooperative Oncology Group-Performance Status (ECOG-PS) score 2–4, and cognitive impairment, and for functional decline in IADL were female sex, fatigue, and risk for depression. Discussion: Functional impairments are frequent in older persons with cancer and a frailty risk profile, and several characteristics are identified that are significantly associated with functional decline. Therefore, FS is an essential part of the geriatric assessment which should be standard of care for this patient population. Next step is to proceed with directed interventions with the aim to limit the risk of functional decline as much as possible.